Faktor-Faktor Mempengaruhi Tingkat Pemahaman Akuntansi Pada Mahasiswa (Studi Kasus Pada Mahasiswa S1 Akuntansi Universitas Dharma Andalas) - Friska Lestari Gultom; Nini (CV. ITTC INDONESIA, 2024)
This research aims to examine the influence of emotional intelligence, learning behavior and learning styles on the level of understanding of accounting at Dharma Andalas University, Faculty of Economics, Bachelor of Accounting Department. This research used 121 respondents. Data collection was carried out using a questionnaire. Determining the sample in this research used a purposive sampling technique, namely by taking samples using certain criteria. The data processing technique used was multiple linear regression analysis with the help of SPSS (Statistical Product and Service Solutions). The results of this research show that Emotional Intelligence has a significant positive effect on the Level of Accounting Understanding, Learning Behavior has a significant positive effect on the Level of Accounting Understanding and Learning Style has a positive effect on Accounting Understanding.